(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The teaching of calculus in the initial training of mathematics teachers allows the development of mathematical and didactic knowledge. The purpose of the study was to characterize the reflections of a group of turquoise preservice teachers when they interacted with a conceptual cartoon contextualized, as a didactic tool, in teaching the concept of derivate as a rate of change. The study used an interpretative approach to the implementation process of this didactic tool in three phases: a. personal reflections and questions that emerge from the cartoon, b. group discussion, and c. group analysis of the final cartoon vignette. The results show the didactic potential of the concept cartoon by favoring the formulation of questions by the preservice teachers, particularly the argumentation from the concepts of differential calculus. Likewise, the contextualized concept cartoon was a mediating narrative in the preservice teachers’ dialogues, doing the constant search for understanding of the cartoon characters’ reasoning logics possible.